Respuesta :

Answer: y+6=-2(x-4)

Step-by-step explanation:

Point slope form: Y-y1=m(x-x1)

Answer:

[tex]y+6=-2(x-4)[/tex]

Step-by-step explanation:

Point-slope form of a line is [tex]y-y_1=m(x-x_1)[/tex] where the slope is [tex]m[/tex] and [tex](x_1,y_1)[/tex] is a point on the line.

We know both of those things so we have enough information without doing any math to do this problem.  You just got to plug in.

So replace [tex]m[/tex] with -2, [tex]x_1[/tex] with 4, and [tex]y_1[/tex] with -6.

Like so:

[tex]y-(-6)=-2(x-4)[/tex].

You can simplify a little:

[tex]y+6=-2(x-4)[/tex].